Exploring Morphological Population Variability: Host Plant and Habitat Dependency in the Protected Moth Gortyna borelii (Lepidoptera, Noctuidae) - László Rákosy; Mihai Alexandru Martin; Geanina Magdalena Sitar; Andrei Crișan; Cristian Sitar (Diversity, 2024)
In this paper, we discuss the evolutionary implications of the correlation between different species of Peucedanum plants and the distribution of Gortyna borelii moth populations in Romania. We highlight geographic separation and isolation among these populations due to anthropogenic landscape fragmentation, which hinders genetic exchange. A geometric morphometric analysis was utilized to visualize and compare the morphometric variations in relation to the environmental variables, particularly the host plant. Additionally, the distribution of G. borelii populations across Europe and in Romania that are correlated with the host plant was analyzed. The significant morphological and morphometric differences between the analyzed populations support our working hypothesis, according to which the use of different Peucedanum species by the larvae of G. borelii leads to an intraspecific diversification correlated with the host plant species. The newly discovered population of G. borelii in Romania holds substantial conservation importance, necessitating protection measures, including demarcating habitat areas and raising awareness among stakeholders. G. borelii is a protected species at the European level (Habitats Directive 92/43/EEC, Appendices II and IV), considered endangered due to the isolation of its populations and anthropogenic pressures exerted through agricultural practices. Understanding the impact of agricultural practices on their habitat is crucial for effective management strategies. Overall, this study sheds light on the complex interplay between ecological adaptation, host plant specialization, and speciation dynamics in phytophagous insects, emphasizing the importance of conservation efforts to preserve G. borelii populations and their habitats.